Study advances in energy finite element method and its application in predicting high-frequency vibration response of aircraft - CHEN Zhaolin; YANG Zhichun (Hangkong gongcheng jinzhan)
The high-frequency vibration problem of structures seriously affects the service safety，reliability and comfort of the aircraft. It is of great academic value and engineering significance to predict the high-frequency vibration response of structures efficiently and accurately. The energy finite element method（EFEM）is a new method developed in recent years to predict high-frequency vibration response. It overcomes the shortcomings of traditional methods such as the finite element method（FEM）and the statistical energy analysis（SEA）in predicting highfrequency vibration response. In this paper，the research progress of the energy finite element method in recent years is reviewed. The basic theory of the energy finite element method and its extension and application in enginee ring are elaborated. Studies of the energy finite element method in predicting the high-frequency vibration response of aircraft structures are introduced. In addition，the future directions of the energy finite element method are prospected.